Abdullayev , Ayyat - (:unkn) unknown (My University, 2026)
Ayyat Abdullayev is a Senior Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction (AzUAC). He holds Bachelor's and Master's degrees in Linguistics from Azerbaijan University of Languages and has been pursuing a PhD in Romance Languages since 2023. His research interests include linguistics, discourse analysis, lexicology, language and media, SMS language, and cognitive approaches to language. He is the author of more than ten scholarly publications, including journal articles, conference papers, course syllabi, and teaching materials. In addition to his teaching and research activities, he serves as Vice Dean of the Faculty of Construction Economics and as an educational expert at AzUAC. He also contributes to the university's internationalization and quality initiatives as a QS Rankings Coordinator and a member of the Faculty Scientific Council and the International Coordinators Group.